The influence of physical education teacher performance on elementary students’ character building - Harry Pramono; Suastika Nurafiati; Tandiyo Rahayu; Sugiharto Sugiharto (LPMPP Universitas Negeri Yogyakarta, 2023)
Students’ character building will be influenced by the school environment as well as their physical education (PE) teachers’ performance. The aim of this research is to analyse and verify the influence of school environment and PE teacher performance on elementary students’ character building. There are 20 elementary schools in Semarang, including 10 public schools and 10 private schools that are used as research samples. The research samples are taken based on cluster random sampling, which is divided into five sectors in Semarang. The qualitative method is applied in this research. The finding shows that the physical education subject gives significant advantages to the development of the students as well as supporting the students’ daily activity based on evaluations by the teacher, school headmaster, and parents. The conclusion attributed to the research is that having a supportive school environment, including facilities and infrastructure, a good proportion of objective competition, a suitable physical education teaching model that is in line with the curriculum, and a supportive and well-competent teacher working in a linear field will have a positive impact on students’ character building. This impact will be visible not only in school but also when the students are home as well